Pengaruh Pembelajaran Cooperative Integrated Reading and Compotition (CIRC) terhadap Hasil Belajar Matematika - Ruyaliningsih Ruyaliningsih (Universitas Indraprasta PGRI, 2017)
Design of this research is experiment in the form of posttest only control design. The research was conducted on the students grade v public Elementary School at Suka Sejati 01 Bekasi , academic year 2015/2016. Sample of this research is taken from two class randomly. After that they are differenciated as experiment class and control class. Both of them got different treatment. Both of class gave posttest in the form of multiple choice test consists of 22 items with 4 choice. Instrument used in the research was validated. Data analysis used t test after the data fulfill a series of normality and homogeneity test. The result of the research show that there are significant impacts of cooperative integrated Reading and Composition (CIRC) learning on Mathematics Achievement.